Review of methodologies for the synthesis of copper (NPsCU) and silver (NPsAG) nanoparticles with different shapes and sizes - Lopez R., Gabriel A. (2017)
Nanoparticles (NPs) are currently the subject of intense scientific research due to a wide variety of potential applications in various fields such as medicine, optics, electronics, nano‐chemistry and agriculture. The properties of these nanostructures depend on their size and shape, and specific properties can be obtained by varying these characteristics. For this reason, a bibliographical analysis was carried out covering different investigators who studied the various methods of synthesis of copper (NPsCu) and silver (NPsAg) nanoparticles, as well as the factors that modify the shape and size of these particles. A main conclusion of this study is that the shape and size of the nanoparticles depend upon factors that can be controlled.